2017
DOI: 10.1007/s00535-017-1377-3
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass to visceral fat area ratio is an important determinant affecting hepatic conditions of non-alcoholic fatty liver disease

Abstract: Decreased muscle mass coupled with increased visceral fat mass is closely associated with an increased risk for exacerbating NAFLD pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 40 publications
5
91
1
Order By: Relevance
“…Shida et al . indicated that changes in body composition were associated with a change in adipokines, myokines, and hepatokines, thus supporting our result that changes in the SF ratio were associated with ALT response. A reduction in body fat and an increase in skeletal muscle could have the greatest impact on liver histology.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Shida et al . indicated that changes in body composition were associated with a change in adipokines, myokines, and hepatokines, thus supporting our result that changes in the SF ratio were associated with ALT response. A reduction in body fat and an increase in skeletal muscle could have the greatest impact on liver histology.…”
Section: Discussionsupporting
confidence: 87%
“…Subjects with high fat mass and low muscle mass had worse clinical outcomes compared with subjects with sarcopenia or obesity alone . Actually, a reduction in skeletal muscle mass could synergistically increase visceral fat in overweight subjects with NAFLD . Although the mechanism underlying this synergy is still unclear, leptin, which stimulates fat degradation in skeletal muscle and improves insulin sensitivity, and inflammatory cytokines such as interleukin‐6 are thought to play a major role in this synergy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of sarcopenic obesity in cirrhosis is multifaceted, with further research required to gain clarity around both clinical and molecular aspects as well as whether sarcopenia or fatty liver is the primary instigator in the muscle‐liver‐adipose tissue axis . Recent reviews have evaluated the pathophysiology of sarcopenia and obesity in cirrhosis and sarcopenic obesity in the general population . Some of the proposed contributing mechanisms are summarized in Figure and include increased pro‐inflammatory markers, decreased physical activity, reduced protein intake, disease‐related reductions in testosterone and growth hormone levels, and ageing …”
Section: Pathophysiology Of Sarcopenic Obesity In Cirrhosismentioning
confidence: 99%